De-territorialized citizenship between place and mobility: the case of Investment Visas in Portugal - Santos, T. R.; Castro, P.; Andreouli, E. (XV PSICAMB Congreso de Psicología Ambiental: Comunidad, recursos y sostenibilidad: el reto de los territorios, 2019)
Introduction: Investment Visas are a legal innovation (Castro, 2012) proposing a de-territorizalized notion of citizenship and migration. It is a (neoliberal) legal framework with concrete consequences in place (e.g. gentrification; Kraehmer & Santangelo, 2018) and in the relationship among migrants (Verkuyten, 2018). This study explores how flow and fixity (Di Masso et al., 2019), informed by this neoliberal legal innovation, affect understandings of place and the migrant community that has made extensive use of it - Chinese nationals. This study will incorporate (1) a press analysis on the meanings associated with Chinese Investment Visas and (2) interviews with key-informants from the Chinese community in Portugal. Study 1 - We collected articles on the Chinese Investment Visas (total n=164) from a tabloid newspaper (Correio da Manhã; n = 81) and a quality one (Público; n= 83) from 2012 until 2017. We analyzed these articles using thematic analysis to explore the meanings of place and mobility associated with the notion of de-territorialized citizenship. Results show citizenship representations informed by cosmopolitanism and free mobility (Andreouli & Howarth, 2017). They also present place as mutually exclusive to mobility, highlighting the economic benefits of this citizenship-by-investment scheme. Study 2 - We then conducted interviews on the everyday practices and understandings of de-territorialized citizenship in the wider community of Chinese migrants in Portugal. We applied snowball sampling to recruit key-informants from the community (total n= 10). We then explore the themes and discursive repertoires (Batel & Castro, 2018) around the meanings associated with Investment Visas. Results show a complementary view of mobility and place. This is accomplished by the mobilization of instrumental and symbolic resources brought to the community by Investment Visas - and the investor-migrant. Conclusion: The Portuguese press and the interviews with Chinese key-informants offer different understandings of the effects of a de-territorialized citizenship and its relationship with place and mobility. Values of cosmopolitanism in the press are mobilized to justify the total absence of the investor-migrant. On the other hand, Chinese key-informants present a different reality, in which place and their relationships are actively transformed to incorporate cosmopolitan ideals. Implications to the study of place in context of migration and mobility facing (neoliberal) legal innovations will be discussed.